CMOS-MEMS resonator parametric variation analysis through equivalent circuit modeling - Mian, M.U. (Institute of Electrical and Electronics Engineers Inc., 2017)
In this paper, we report a micro electro mechanical system (MEMS) shuttle resonator fabricated on CMOS-MEMS wafer technique. The resonator operates at the resonant frequency when a current flows through the metal layers in the presence of an external magnetic field. We investigate the resonant frequency and amplitude shifts due to parametric variation in beam length, width, and structure thickness in resonator motion. The theoretical formulation of the equivalent circuit model is presented. Simulation of resonator with variations are carried out using equivalent circuit model, these variations are based on fabrication foundry tolerance range. Simulation results show a range of operational frequencies in which the resonator can perform under the fabrication tolerances provided by the foundry. © 2016 IEEE.